1974
DOI: 10.1159/000136547
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen-induced Hepatic Necrosis

Abstract: The relationship between the metabolic disposition of acetaminophen and the susceptibility of hamsters, mice and rats to acetaminophen-induced liver necrosis has been examined. The fraction of low doses of acetaminophen converted to the mercapturic acid metabolite was highest in the most susceptible species (hamsters, mice), and lowest in the more resistant species (rat). Pretreatment regimens known to potentiate the hepatotoxicity increased mercapturic acid formation whereas treatments which protect from live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
0
1

Year Published

1978
1978
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 515 publications
(120 citation statements)
references
References 18 publications
0
97
0
1
Order By: Relevance
“…Emerging case reports indicate that hepatotoxicity may also occur with chronic therapeutic use of paracetamol, even in the absence of risk factors such as chronic alcoholism and malnutrition [Bolesta and Haber, 2002]. Bioactivation of paracetamol to its toxic metabolite via cytochrome P450 (CYP) 2E1, and subsequent binding of the toxic metabolite to liver macromolecules is responsible for hepatocyte damage and death, as described in Table 3 [ Prescott, 1983;Jollow et al 1974;Mitchell et al 1973]. Liver biopsy reveals a centrilobular necrosis, with periportal sparing and little or no inflammatory reaction [Ward and AlexanderWilliams, 1999;Prescott, 1983].…”
Section: Pharmacokinetic Changesmentioning
confidence: 99%
“…Emerging case reports indicate that hepatotoxicity may also occur with chronic therapeutic use of paracetamol, even in the absence of risk factors such as chronic alcoholism and malnutrition [Bolesta and Haber, 2002]. Bioactivation of paracetamol to its toxic metabolite via cytochrome P450 (CYP) 2E1, and subsequent binding of the toxic metabolite to liver macromolecules is responsible for hepatocyte damage and death, as described in Table 3 [ Prescott, 1983;Jollow et al 1974;Mitchell et al 1973]. Liver biopsy reveals a centrilobular necrosis, with periportal sparing and little or no inflammatory reaction [Ward and AlexanderWilliams, 1999;Prescott, 1983].…”
Section: Pharmacokinetic Changesmentioning
confidence: 99%
“…However, in overdosage it can cause acute hepatic necrosis through the formation of a highly reactive intermediate metabolite by hepatic cytochrome P-450 dependent microsomal enzymes (Mitchell et al, 1973;Mitchell et al, 1974). In most laboratory animal species, the hepatotoxicity of paracetamol is increased by pretreatment with microsomal enzyme inducers such as phenobarbitone, 3-methyl-cholanthrene and ethanol and decreased by inhibitors such as piperonyl butoxide (Mitchell et al, 1973;Mitchell et al, 1974;Jollow et al, 1974;Strubelt, Obermeier & Siegers, 1978;Teschke, Stutz & Strohmeyer, 1979;Streeter & Timbrell, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in experimental animals have shown that when higher doses are given, a reactive metabolite of the drug binds covalently with liver cell protein (5,7,8). Thorgeirsson et al (9) demonstrated that changes in bio chemical parameters were noted in both male mice and male hamsters after AAP admin istration.…”
Section: Abstract-studiesmentioning
confidence: 99%